CEREBRAL VENOUS THROMBOSIS IN THE PEDIATRIC AGE GROUP: TWENTY-YEAR EXPERIENCE - JL Sion; DM Celeste; MP Garanito; JDA Carneiro (Hematology, Transfusion and Cell Therapy)
Aim: Describe the clinical profile, treatment, and outcome of the patients with Cerebral Venous Thrombosis (CVT). Materials and methods: Single-center retrospective study of pediatric CVT patients (< 18y) treated between October 2003 and December 2023. Results: We analyzed 44 patients,59.1% were male;median age 5.6 years (1 day-16.1).Headache (40.9%), seizure (27.3%) and vomit (27.3%) were common presenting clinical features.CT or MRI scans were performed in 65.9% of the patients, and 34.1% presented intracranial hemorrhage at the admission.Sigmoid sinus (61.4%), sagittal (59.1%), and transverse (52.3%) were the common sites of thrombosis.Risk factors included infection (47.6%), catheter (21.4%), cancer (18.2%), and head trauma (15.9%).All patients with trauma presented bleeding at the diagnosis, and 2 patients (4.5%) required surgical intervention.Fourty-one patients (93.2%) received anticoagulant therapy (low molecular- weight heparin, 78.0%; unfractionated heparin, 18.2%).Two patients (4.5%) had no clinical condition to treat, and one (2.3%) lost follow up.None patient underwent mechanical thrombectomy.One patient (2.3%) on anticoagulant therapy experienced major bleeding.Partial recanalization was achieved in 23 (59.0%), and complete recanalization in 16 (41.0%).Eight patients (18.2%) presented neurological sequelae. No child died due to thrombosis or treatment.Thrombophilia tests were performed in 3patients (6.8%), without risk factors identified.High lipoprotein (a) [Lp(a)], lupus anticoagulant (LAC), and heterozygous protein S deficiency were detected.In addition, 18 patientswith identified triggers underwent thrombophilia screening,and 55.5% presented a positivetest result (4: high Lp(a), 2: LAC, 3: prothrombin G20210A mutation, 1: heterozygous protein C deficiency). Discussion: The age distribution of pediatric thrombosis is bimodal, revealing peaks in neonates and adolescents. CVT is common in neonates (40%) because they have lower concentrations of anticoagulant proteins, and some patients have congenital heart disease. Our median age (5,6y) probablyi s related to the limited hematological evaluations requested in the neonatal ICU and the cardiology unit.Our results are consistent with literature. In children, the most common symptoms are headache, vomit and altered level of consciousness;and the main risk factors are contiguity head and neck infections, cancer, catheter, and head trauma.In spite of the anticoagulant treatment in the acute phase is controversial, due to an increased risk of hemorrhage during treatment, fourty-one patients (93.2%) were treated, and our frequenceof major bleeding was similar with the literature (2.3-6.0%), without any death.According to literature, the overall mortality rate that varies from 3.0 to 4.2%. Although many studies suggest that thrombophilia screening is unnecessary in patients with an identified trigger factor, 10 patients (55.5%) presented a positive thrombophlia test result. Despite de limitations of our study, this prompts us to reconsider whether thrombophilia screening should be performed for our patients, as such identification could influence their management. Conclusion: Pediatric CVT is rare,requiring early suspicion, and diagnosis. Although treatment issues are not well defined, there is evidence that anticoagulation has an important role in all age groups. Clinical trials are essential to address the optimal therapeutics, efficacy, morbidity and mortality in this disease.